2008
DOI: 10.1016/j.jtcvs.2008.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Constrictive external nitinol meshes inhibit vein graft intimal hyperplasia in nonhuman primates

Abstract: By using an animal model that addressed the clinical phenomenon of diameter discrepancy between vein graft and bypassed artery, we could demonstrate that suppression of intimal hyperplasia required constrictive mesh sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 26 publications
4
96
0
Order By: Relevance
“…The authors reported that the vein graft that was constricted by 50% in a baboon model showed significantly suppressed intimal hyperplasia at both 6 and 12 weeks when compared to the unsupported vein grafts. Additionally, the authors demonstrated that only in the 50% constricted vein graft was endothelialization maintained (Zilla et al, 2008). Although the authors demonstrated some pulse compliance in a subsequent knitted nitinol wire mesh study, wire breakage and www.frontiersin.org a lower degree of surface endothelialization was observed (Zilla et al, 2011).…”
Section: Autologous Graftsmentioning
confidence: 97%
See 2 more Smart Citations
“…The authors reported that the vein graft that was constricted by 50% in a baboon model showed significantly suppressed intimal hyperplasia at both 6 and 12 weeks when compared to the unsupported vein grafts. Additionally, the authors demonstrated that only in the 50% constricted vein graft was endothelialization maintained (Zilla et al, 2008). Although the authors demonstrated some pulse compliance in a subsequent knitted nitinol wire mesh study, wire breakage and www.frontiersin.org a lower degree of surface endothelialization was observed (Zilla et al, 2011).…”
Section: Autologous Graftsmentioning
confidence: 97%
“…The authors adopted a loose-fitting macroporous polyglactin stent for bilateral saphenous vein into common carotid artery interposition grafting in Large White pigs. At 1 and 6 months, the stented vein grafts showed decreased neointimal and medial thickening compared to unstented controls (Vijayan et al, 2004); however, the use of relatively small saphenous veins for interposition grafts in large arteries may have created flow conditions not clinically observed in bypass graft surgery (Zilla et al, 2008).…”
Section: Autologous Graftsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some stents, however, are placed around the outside of the graft, as an external, supporting sheath [17,45]. Lesions treated with internal stents have a reduced incidence of restenosis (compared with angioplasty alone) in large arteries with short lesions [46,47], but require a longer hospital stay with the possibility of more vascular complications that may not be amenable to emergency surgical correction [46,48].…”
Section: Management Strategies For Atherosclerosismentioning
confidence: 99%
“…Updated therapeutic strategies to alleviate restenosis or neointimal hyperplasia correspondingly have included collection and preservation of the vein, pharmacotherapy, gene therapy, radiotherapy, and laser and photodynamic therapy. 4,5 These treatments have shown inhibitory effects on restenosis in animal trials, but still have some drawbacks.…”
Section: Introductionmentioning
confidence: 99%